Determinants of financial governance practices: Evidence from NGOs in ghana - Fiador, V. O. (My University, 2013)
Purpose – The purpose of this paper is to explore financial governance as practiced by NGOs in Ghana and further examines the determinants of the financial governance structures of the NGOs. The study specifically investigates which organizational-level characteristics exhibit any link whatsoever with governance as it relates to budget preparation, budget execution and internal controls and budget monitoring. Design/methodology/approach – Using a questionnaire to conduct the survey, a cross-sectional regression analysis was executed. Findings – The findings of the study indicate that the most positively influential factor in explaining an NGO’s adoption of a governance framework is its size. The other variables, organizational age and independence, are not significant across all three financial governance proxies and when they prove significant, the effect is negative. Originality/value – The findings hold important policy implications and especially so for countries that attract significant funding via relatively small-sized NGOs.
Keywords: Financial governance, NGO, Organizational demographics, Size, Non-governmental organizations,Ghana